2011
DOI: 10.4302/plp.2011.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spectra of materials measured by Time Domain and Fourier Transform Spectroscopy in Terahertz range

Abstract: Abstract-Absorption spectra in THz range of commonly used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, the main characteristics of electromagnetic waves absorbed, reflected, and radiated by such materials are usually in the terahertz, mid to far infrared, and optical bands 2,3 , Schoenes et al 4 and Devetter et al 5 found through experimental measurements that the characteristic peak of UO2's reflection spectrum is in the 8-18 THz range, while the optical reflection spectrum is in the 2.5-0.096um (120-3120 THz) range. For lower purity massive uraninite, the main characteristic of its reflection spectrum is in the 6-18 THz range; Palka et al 6 and Isbell et al 7 demonstrated through experimental research that the main components of the nuclear bomb detonating explosive PBX, including RDX, HMX, and PETN, exhibit reflectance spectra with main characteristics ranging from 0.5 to 3.5 THz and 2-25 um (150-12THz). The above materials exhibit weak reflection signals of less than 20% in the optical and near-infrared bands, which are easily masked by signals from the background environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main characteristics of electromagnetic waves absorbed, reflected, and radiated by such materials are usually in the terahertz, mid to far infrared, and optical bands 2,3 , Schoenes et al 4 and Devetter et al 5 found through experimental measurements that the characteristic peak of UO2's reflection spectrum is in the 8-18 THz range, while the optical reflection spectrum is in the 2.5-0.096um (120-3120 THz) range. For lower purity massive uraninite, the main characteristic of its reflection spectrum is in the 6-18 THz range; Palka et al 6 and Isbell et al 7 demonstrated through experimental research that the main components of the nuclear bomb detonating explosive PBX, including RDX, HMX, and PETN, exhibit reflectance spectra with main characteristics ranging from 0.5 to 3.5 THz and 2-25 um (150-12THz). The above materials exhibit weak reflection signals of less than 20% in the optical and near-infrared bands, which are easily masked by signals from the background environment.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is that the radiation could be used to detect dangerous * E-mail: jung@if.pw.edu.pl materials. Because of the fact that the emissivity of many explosive materials such as Hexogen (RDX), Penthryte (PETN), Octogen (HMX) has some characteristic transmission features in the THz region [4,5]. In our work, a screening camera TS4 from ThruVision Systems Ltd. [6] operating in the THz range was tested in a smoky environment.…”
mentioning
confidence: 99%
“…In order to check the influence of smoke on transmission in the THz range, we exploited Time Domain Spectroscopy (TDS) [2,4,5] . The TDS gives us opportunity to measure transmission in the (0.1 ÷2.5)THz range.…”
mentioning
confidence: 99%